Pembelajaran Keterampilan Membaca (Maharah Qiraah) Menggunakan Koran Elektrronik (Al-Jaridhah Al-Elektroniyah) - Mohammad Zainal Hamdy (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Abstract: This research consists of two problems. Firstly, how is the process of learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasan. Secondly, What is the Factors of learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasan. This research uses qualitative research and the data source includes the teachers and students of learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasan. And then,Data collection techniques using interviews and observationswhere the research was carried out for one month. Start from 2nd of February 2020 untill 3rd of March 2020 that the data analysis using descriptive analysis. The results of this research state that the process of learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasanare effectiveexcept some problems like vocabulary difficulties in contemporary languages. So for all of students who studies this learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasanis hoped to take the time to memorize difficult vocabularies, especially in contemporary languages. And for the teachers who teaches learning reading skills using electronic newspapers at Darul Lughah wal Qur’an Boarding School Angsokah Timur Palengaan Daya Palengaan Pamekasan could be more creative and innovate so that students love Arabic more than before and they are not bored in following their learning.